Urine NGAL and IL-18 are Predictive Biomarkers for Delayed Graft Function Following Kidney Transplantation - Chirag R. Parikh; Alkesh Jani; Jaya Mishra; Qing Ma; Caitlin Kelly; Jonathan Barasch; Charles L. Edelstein; Prasad Devarajan (2006)
Delayed graft function (DGF) due to tubule cell injury frequently complicates deceased donor kidney transplants. We tested whether urinary neutrophil gelatinase-associated lipocalin (NGAL) and interleukin-18 (IL-18) represent early biomarkers for DGF (defined as dialysis requirement within the first week after transplantation). Urine samples collected on day 0 from recipients of living donor kidneys (n = 23), deceased donor kidneys with prompt graft function (n = 20) and deceased donor kidneys with DGF (n = 10) were analyzed in a double blind fashion by ELISA for NGAL and IL-18. In patients with DGF, peak postoperative serum creatinine requiring dialysis typically occurred 2-4 days after transplant. Urine NGAL and IL-18 values were significantly different in the three groups on day 0, with maximally elevated levels noted in the DGF group (p < 0.0001). The receiver-operating characteristic curve for prediction of DGF based on urine NGAL or IL-18 at day 0 showed an area under the curve of 0.9 for both biomarkers. By multivariate analysis, both urine NGAL and IL-18 on day 0 predicted the trend in serum creatinine in the posttransplant period after adjusting for effects of age, gender, race, urine output and cold ischemia time (p < 0.01). Our results indicate that urine NGAL and IL-18 represent early, predictive biomarkers of DGF.